Botcrafting and Botbreeding : A Simplified Economics of Evolutionary Algorithms - Aberkane, Idriss (Sens public)

(untitled) (Département des littératures de langue française, 2016)
Let us consider the industrial and economic impact of genetic programming and its generic availability to the masses. Is the interaction between genetic programming and the so-called “cognitariat” the beginning of a “genetic revolution” in the industrial sense ? Can we theorise a genetic marketplace, based on the dynamic of bids and asks for genetic algorithms to be made-to-order and leverage any daily routine, thus trading value ? Can genetic algorithms be crossbred to achieve a phenomenon similar to animal domestication, with a transition from wild to domestic type and heterosis, and can such a pressure for domestication percolate to macroeconomic value ? Which economic marketplace would allow such an economic phenomenon to happen and percolate least impeded ? Here I consider the economic implication of evolving genetic algorithms to address any repetitive human task, within a grand genetic marketplace composed of bidders and askers that would be using, evolving and breeding genetic programs (“bots”) and manipulating them as “bot breeders” to leverage their own economic output. I define a cryptocurrency on the buyer’s side, conceived to represent a unit of genetic purchasing power, which I call a “botcoin”.